Influence of sodium hypochlorite on cyclic fatigue resistance of nickel–titanium instruments: A systematic review and meta-analysis of in vitro studies - dos Reis-Prado, Alexandre Henrique; Abreu, Lucas Guimarães; de Arantes, Lara Cancella; dos Santos de Paula, Kiani; de Castro Oliveira, Sabrina; Goto, Juliana [UNESP]; Viana, Ana Cecília Diniz; Benetti, Francine (Springer Nature, 2023)
Objective: This systematic review/meta-analysis investigated the influence of NaOCl on cyclic fatigue resistance of endodontic NiTi instruments. Materials and methods: A systematic search until July 2022 in PubMed/MEDLINE, Embase, Scopus, Web of Science, SciELO, Cochrane Library, and grey literature was conducted. According to the PECOS strategy, only in vitro studies evaluating the effects of NaOCl on the cyclic fatigue resistance of NiTi instruments were eligible. Cyclic fatigue resistance was the primary outcome. A modified Joanna Briggs Institute’s Checklist was used for risk of bias assessment. Results: Of the 2,445 records screened, 37 studies were included. Most studies used simulated canals made of stainless-steel block with severe to moderate curvatures. NaOCl concentration varied from 1–6%, mainly at 37 °C. Regarding fatigue resistance, 23 studies using 1.2% to 6% NaOCl showed a reduction in the resistance compared to the control groups, especially when pre-heated. Four meta-analyses were performed according to the tested NiTi systems. The meta-analyses indicated that the PTU F2 files had higher reduction of fatigue resistance after exposure to 5.25% NaOCl; no differences between NaOCl and no immersion were observed for Reciproc R25, WaveOne 25.08, and WaveOne Gold Primary files. Included studies had low risk of bias. Conclusion: NaOCl appears to reduce cyclic fatigue resistance of certain NiTi files, especially when they are pre-heated, particularly in conventional NiTi files compared to some heat-treated instruments. It is possible that the temperature of the solution may have a greater influence on resistance than NaOCl itself. Important to note that an overall tendency toward no significant influence was observed among various systems. Clinical relevance: Precautions are necessary when a pre-heated high-concentration NaOCl is used to enhance its properties during root canal preparation, mainly using conventional wire.
Keywords: Cyclic fatigue resistance; Meta-analysis; Nickel-titanium instruments; Root canal irrigants; Sodium hypochlorite; Systematic review